تاريخ الملاحة البحرية الملايوية: بزوغها وتموقعها الإستراتيجي ودورها في تطور التجارة البحرية الدولية: The Malay Maritime: Its History and Strategic Role in the Development of the International Maritime Trade - Ahmad Hj Osman, Rahmah Bt; Yaapar, Md. Salleh; Muhammad, Latifah Najihah; Hamawiya, Adham Muhammad Ali (Journal of Al-Tamaddun, 2023)
This paper aims to highlight the history of Malay maritime from its start until the end of the 14th century by identifying its geographical area and finding out its most important centers, tools, and relations with the great powers to discover their role in the development of maritime trade. Then, this paper describes the lost history in the studies of the Malay maritime history. The paper employes the descriptive approach based on reviewing the historical events in the relevant sources. Thus, the paper finds that the history of Malay maritime was full of great achievements and played an important role in the regions. Particularly, its presence in Malacca as an effective strategic center and owning the largest and most important commercial vessels. The paper also shows that this effective role of Malay nation has been reflected in the economic, social, and cultural developments and global maritime trade. Therefore, it is recommended for researchers to direct more efforts into history and research to learn more about this history of Malay maritime.